Analisis Pasangan Capres dan Cawapres pada Pemilu 2024 Perspektif Maqashid al-Syari’ah - Najib, Afifun Najib; Salikin, Adang Djumhur; Najib, Agus M (Cv. Kalimasada Group, 2025)
This study analyzes the presidential and vice presidential candidate pairs in the 2024 election using the Maqashid al-Syari'ah approach. This research is classified as normative-explanatory research, namely studying, explaining, and explaining descriptively qualitatively with a textual and actualist approach. Research data were obtained through a literature study of the vision and mission of each candidate and their track record. The analysis was carried out by examining the vision and mission of each candidate. The research findings show that the presidential and vice presidential candidate pairs in the 2024 election from the Maqashid al-Syari'ah perspective can be analyzed from their textual and actualist approaches. Based on the textual perspective, the vision and mission of the presidential and vice presidential candidate pairs are a benchmark that can be used as a guideline for channeling the voting rights of each voter. Meanwhile, the actualist perspective states that the track record and experience of each presidential and vice presidential candidate pair are the leverage of each electability. In conclusion, the vision and mission of the presidential and vice presidential candidate pairs in the 2024 election from the perspective of Maqashid al-Syariah is a tool to measure the level of welfare and benefits for Indonesian citizens.